Lab-on-fiber sensing system based on responsive Fabry–Perot optical resonance cavities prepared through in situ construction strategy. (22nd July 2021) - Wang, Guangrong; Chen, Dan; Wang, Tieqiang; Chen, Hongxu; Zhang, Xuemin; Li, Yunong; Zhang, Liying; Fan, Fuqiang; Fu, Yu
Abstract: For decades, lab-on-fiber (LOF) sensing systems have become an emerging optical sensing platform due to the features of small size and light weight. Herein, a simple and efficient in situ construction strategy was reported for the preparation of LOF sensing platform based on the integration of responsive Fabry–Perot optical resonance cavity on optical fibers. The responsive Fabry–Perot optical resonance cavity with thermal poly(N-isopropylacrylamide) polymer brush layer sandwiched by two silver layers was constructed on the end surface of the optical fiber through combining in situ surface-initiated polymerization and metal film deposition techniques. Owing to the thermo-responsiveness of the intermediate layer, the as-prepared LOF sensing system shows a sensitive response towards the environmental temperature. Importantly, the as-prepared LOF sensing system also possesses excellent repeatability and rapid response rate. Together with the features of high sensitivity, excellent repeatability and rapid response rate, we believe such LOF sensing system will provide a foundation for the future applications of medical diagnosis, in vivo detection and public security.